Små barns medvirkning i samlingsstunder - Eide, Brit Johanne; Os, Ellen; Pramling Samuelsson, Ingrid (Nordisk barnehageforskning, 2012)
Title: Young children’s participation during circle time. Abstract: In day schedules of early childhood education, circle time has traditionally been one of the core situations. According to the Convention on the Rights of the Child, children should be given opportunity to influence their everyday life. This article presents an analysis of circle time in 8 toddler groups. The focus of the analysis is children’s opportunities to participate and take part in the process of decision-making during circle time. The results indicate that the toddlers take part in community of the group, but their opportunities to influence are limited.